Normal Automorphisms of Free Burnside Groups of Period 3 - Atabekyan, Varujan; Aslanyan, H.T.; Grigoryan, A. E. (Armenian Journal of Mathematics, 2017)
If any normal subgroup of a group $G$ is $φ$-invariant for some automorphism $φ$ of $G$, then $φ$ is called a normal automorphism. Each inner automorphism of a group is normal, but converse is not true in the general case. We prove that any normal automorphism of free Burnside group $B(m,3)$ of period 3 is inner for all rank $m\ge3$.
Keywords: normal automorphism, inner automorphism, periodic group, free Burnside group, free group